2017
DOI: 10.3892/mmr.2017.8252
|View full text |Cite
|
Sign up to set email alerts
|

Lower level of IL‑35 and its reduced inhibition in Th17 cells in patients with bone marrow mononuclear cells Coombs test‑positive hemocytopenia

Abstract: Interleukin (IL)-35 is the latest member of IL-12 family, which plays an important role in other autoimmune diseases. Bone marrow mononuclear cells Coombs test-positive hemocytopenia, also termed immunorelated hemocytopenia (IRH) is a type of autoimmune-associated diseases. The present study investigated the relationship of IL-35 in patients with IRH. A total of 43 patients with IRH and 19 normal controls were enrolled in the current study. Serum levels of IL-35 and IL-17 in peripheral blood were evaluated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
7
1
Order By: Relevance
“…However, Th17 cells frequency, RORγt mRNA, or IL-17 secretion by CD4 + T cells did not change notably in response to IL-35 stimulation. This was not consistent with the previous results in coxsackievirus-B3-induced myocarditis [41] and hemocytopenia [42], in which Th17 cells was strongly inhibited by delivery of IL-35. This might be partly due to the difference status of chronic and acute viral infections.…”
Section: Discussioncontrasting
confidence: 98%
“…However, Th17 cells frequency, RORγt mRNA, or IL-17 secretion by CD4 + T cells did not change notably in response to IL-35 stimulation. This was not consistent with the previous results in coxsackievirus-B3-induced myocarditis [41] and hemocytopenia [42], in which Th17 cells was strongly inhibited by delivery of IL-35. This might be partly due to the difference status of chronic and acute viral infections.…”
Section: Discussioncontrasting
confidence: 98%
“…IRH is a special type of bone marrow failure syndrome. The bone marrow microenvironment is dynamic, and is composed of growth factors and stromal cells (3)(4)(5). Endothelial progenitor cells (EPCs) are one of the important Original Article components and play a significant role in the bone marrow microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial progenitor cells (EPCs) are one of the important Original Article components and play a significant role in the bone marrow microenvironment. Previous studies have shown that EPCs regulate the transport and homing of hematopoietic stem cells (4,5), and are related to the delayed recovery of hematopoietic stem cells after transplantation (6)(7)(8). Moreover, the number and function of EPCs in patients with poor chimeric function after transplantation are significantly different from those with good chimeric function, and atorvastatin can improve this difference (9).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion balance of Th1/Th2 cells shifted to the Th2 direction [11]. The quantity and function of Th17 cells, which was named follicular helper T cells, increased [12][13][14], while Tregs and NK cells decreased in the IRP patients [14,15]. The proportion balance of pDC/mDC cells shifted to the pDC direction [16].…”
Section: Introductionmentioning
confidence: 99%